Diversity and traditional use knowledge of medicinal plants among communities in the South and South-Eastern zones of the Tigray Region, Ethiopia - Mengistu, Dejene Kassahun; Jemal, Mohammed N.; Gebrehawaryat Kidane, Yosef; Fadda, Carlo (MDPI, 2022)
In the present study, the diversity of medicinal plants (MPs) and associated traditional knowledge of rural community herbalists to treat human and animals’ diseases were assessed in two districts in the Tigray Region, Ethiopia. Study participants were randomly selected for survey and focus group discussions, while key informant traditional healers were identified through snowball/chain-referral sampling. The informant consensus factor (FIC) by ailment category and fidelity level (FL) for some MPs were determined. About 97 MP species were identified. Leaves, roots, and seeds are the parts predominantly used for phytomedication preparation to treat 30 human and 5 animal diseases. Diseases, such as epilepsy, arthritis, otitis media, and fever, are treated with a combination of 2–4 MPs. The FIC value ranged from 0.29–1.00, with most human diseases showing an FIC value of above 0.7. The FL value for the MPs ranged from 53–100%, with plants used to treat more than one disease tending to have lower FL values. Higher values of FIC and FL indicate high levels of traditional knowledge used to identify and administer medicinal preparations. Despite the frequent use of MPs, the four-cell analysis showed that most of them risk extinction due anthropogenic and climate factors. We recommend botanical gardens as a solution to sustainable conservation, study, education and a source for these declining MP species.